Desire and time in modern English fiction : 1919-2017 - Dellamora, Richard (New York, NY : Routledge, Taylor & Francis Group, 2021)
Beginning with Somerset Maugham's innovative, sexually dissident South Seas novel and tales and Alfred Hitchcock's gay-inflected revisiting of the Jack the Ripper sensation in silent film, this book considers the continuing presence of the past in future-oriented work of the 1930s and the Second World War by Sylvia Townsend Warner, Virginia Woolf, George Orwell, and the playwright and novelist, Patrick Hamilton. The final three chapters carry the discussion to the present in analyses of works by lesbian, postcolonial, and gay authors such as Sarah Waters, Amitav Ghosh, and Alan Hollinghurst. Focusing on questions about temporality and changes in gender and sexuality, especially gay and lesbian, straight and queer, following the rejection of the Victorian patriarchal marriage model, this study examines the continuing influence of late Victorian Aestheticist and Decadent culture in Modernist writing and its permutations in England.
6 Sexual Politics and Blackout in Patrick Hamilton's Rope, Gaslight, and Hangover Square -- 7 George Orwell, Futurity, and Male Homosexual Panic -- 8 Queering Past-and Future-in Sarah Waters' Affinity -- 9 Ecological Time and Social Desire in Amitav Ghosh's The Hungry Tide -- 10 Male Homoerotics in the Metamodernist Fictions of Alan Hollinghurst -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Desire in literature; English literature -- 20th century -- History and criticism; English literature -- 21st century -- History and criticism; LITERARY CRITICISM / General